Triple Helix as a Social and Legal Phenomenon of Regional Innovative Development: on the Example of the Penza Region as an Average Subject of the Russian Federation - Fomin, Alexey (LeXonomica, 2019)
The experience of developed countries (Germany, USA, Scandinavia) shows that scientific, technical and innovation activities contribute to modernization of the economy, and are a stabilizing factor in social development. Coordination and structuring of such a relationship at the legislative level is the basis of strategic planning of Russia and its regions. Today, the creation of new constitutional, social and legal foundations of strategic development affects every constituent entity of the Russian Federation. The article analyses the need to fill a gap in legal research, the development of scientific and theoretical provisions related to innovation. The Penza region is a typical constituent entity of the Russian Federation, taking into account the peculiarities of the geographical location, the number and well-being of the population, the development of the business sector, and the level of scientific potential. Standard socio-economic problems of the state, as well as the resulting status of innovative development are characteristic for the Penza region. In the article particular attention is paid to the non-hierarchical way of coordinating “government-business-science” relations in the context of the Triple Helix model, which plays a key role in the innovation process as a social and legal mechanism of development of economy.